Retinol-binding protein 4 is associated with arterial stiffness in early postmenopausal women. Issue 8 (August 2020) - Chondrou, Asimina; Nigdelis, Meletios P.; Armeni, Eleni; Augoulea, Areti; Rizos, Dimitrios; Kaparos, George; Alexandrou, Andreas; Goulis, Dimitrios G.; Patras, Raphael; Aivalioti, Evmorfia; Stamatelopoulos, Kimon; Lambrinoudaki, Irene V.
Abstract: Objective: Recent evidence in postmenopausal women suggested lack of association between serum levels of retinol-binding protein 4 (RBP4) and subclinical atherosclerosis; however, associations with arterial stiffness in this population remain unexplored. We evaluated the association among RBP4 and cardiovascular risk factors, including homocysteine, a marker involved in retinoic acid synthesis, and indices of arterial stiffness, in a sample of apparently healthy postmenopausal women. Methods: This cross-sectional study included 123 healthy postmenopausal women, not on hormone therapy, antihypertensive, or hypolipidemic treatment and with a menopausal age 10 years or less. We performed biochemical/hormonal assessment and sonographic evaluation, including carotid-femoral pulse wave velocity (PWV) and carotid artery stiffness index (SI). Results: Univariate analysis showed that RBP4 values correlated with age, low-density lipoprotein-cholesterol and estradiol levels. There was a trend of association of SI and PWV with homocysteine and triglycerides. RBP4 differed according to PWV, using the median PWV value as cut-off (RBP4, PWV ⩽8.1 vs >8.1 m/s: 10.09 ± 2.05 vs 10.85 ± 1.91 ng/mL, analysis of covariance P value 0.014 adjusted for age, menopausal age, estradiol, pulse pressure). Linear regression analysis showed that PWV was independently associated with RBP4, age, and pulse pressure, whereas SI was independently associated with RBP4. An increase of one standard deviation in RBP4 levels (2.54 ng/mL) was associated with an increase of 0.577 m/s in PWV. Conclusions: RBP4 serum levels are associated with arterial stiffness, in a sample of healthy postmenopausal women. If this association is causative, serum RBP4 levels could serve as a marker of arterial stiffness. Prospective studies are required to investigate the significance of our findings. N/A: Video Summary: http://links.lww.com/MENO/A621 . Abstract : Supplemental Digital Content is available in the text